(untitled) (Baghdad Science Journal, 2012)
Seeds of Nigella sativa were sown in containers containing 15kg Loamy soil. The seeds were divided before sewing into two groups. The first group was soaked with ordinary tap water end the second group was treated with magnetized water for 24hrs. The irrigation process was completed until 75% of capacity field with two types of water (tap water of magnetized water with three replications).The magnetized water was obtained from special electric device designed for this purposeRecorded measurements (plants height, the number of branches/ plant, dry weight ofplant, number of flowers, 1000 seed weight) during the harvest period.Results indicated that the seed group which was treated with magnetized water was more significant than the one which was treated with the normal water in all the studied characteristics.